Madurese Language in West Kalimantan Context: The Overlapping of Social Groups and the Enactment of Social Identity. - Muhammad Ali (IKIP PGRI Pontianak, 2021)
This article discusses the linguistic shift experienced by the Madurese language used in West Kalimantan as well as the socio-cultural influences on the creation of a linguistic variation of the language. This language which was brought by the Madurese people as immigrants from Madura Island to West Kalimantan in the 18th century has transformed into a new variety of a language as the result of having direct and close linguistic encounters with the local language. The transformation seems to be apparent in the introduction of Malay-rooted lexical items and the understanding of Madurese stratification. It, in turn, has led to the construction of a new variety of the language as well as the creation of a new social identity for Madurese people in Kalimantan.